2007
DOI: 10.1504/ijil.2007.011689
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative commerce through Web-Based Information Integration technologies

Abstract: There is a great potential for the establishment of Web-Based Information Integration (WBII), to help people share information on the Internet, especially in B2B and B2C applications. This integration of internal systems brings employees from the many seemingly separate areas of retail, catalogue, online, finance, distribution, merchandising and training to function as a total systems integrated system. With collaborative commerce becoming a necessity, executives will begin emphasize ways in that people and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…According to Ref. [4][5][6], a service orchestration tool should have four characteristics of versatility, expression richness, output standards as well as friendly man-machine interface. Although BPEL can describe in what order, where to call Web services as well as how to organize these calls, but it cannot store and operate the data in business process.…”
Section: Services Orchestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ref. [4][5][6], a service orchestration tool should have four characteristics of versatility, expression richness, output standards as well as friendly man-machine interface. Although BPEL can describe in what order, where to call Web services as well as how to organize these calls, but it cannot store and operate the data in business process.…”
Section: Services Orchestrationmentioning
confidence: 99%
“…Some new manufacturing patterns including supply chain management [4], collaborative commerce [5], extended enterprise [3], virtual enterprise [3,[6][7][8], dynamic alliance [9], customer relationship management, e-business, etc., are developed. All of these new patterns form the basic features of a networked enterprise.…”
Section: Introductionmentioning
confidence: 99%
“…It helps companies source input products and services at the lowest cost, while ensuring that those inputs meet technical and other specifications. By making this process web-based, e-procurement solution providers are changing the process in ways that go far beyond its mere computerisation and automation (Johnson and Whang, 2002;Smith, 2005;Smith, 2007a;Smith, 2007b). According to Wheatley (2003), it was found that 17% of companies that do not yet have sourcing and procurement applications plan to implement in the near future and between 2002 and 2003, there was a market growth of 12%, up from $1.7 billion in 2002 to $1.8 in 2003.…”
Section: E-procurement Strategically Leveraging B2b Capabilitiesmentioning
confidence: 99%
“…With graphical displays, user interfaces, and programmable drives, the computer is the obvious champion for the virtual classroom (Smith, 2004a;Smith, 2004b;Wu and Chen, 2008). However, it is just a tool to access the open sources found available on the internet (Smith, 2006;Smith, 2007). The internet provides a channel and connection between users, allowing them to translate physical thought into digital and numeric data, and then communicating the messages from user to user.…”
Section: Technology Considerationsmentioning
confidence: 99%
“…For teachers of virtual classrooms, working part-time is a possibility because of the flexible nature of e-learning (Smith, 2007;Gallien and Oomen-Early, 2008). The teacher is not required to work from an office or classroom to instruct lessons or organise material and lessons; this can be done from anywhere where they have access to a computer with an internet connection and other necessary software/hardware, which is an advantage.…”
Section: Positive Attributes Of Virtual Classroomsmentioning
confidence: 99%